Research and development of complex access control systems." [Tender documents : T26775908] (MENA Report, 2015)
Systems controlling access to protected areas if a secure area intended only to authorized persons, usually used to protect the weak and easy to overcome the elements, devices or methods (physical, mechanical barriers, signaling means ...). at the forefront are nowadays getting integrated control systems using input physical characteristics of a person that can not be stolen or misused. for access control system can be used in several ways. one option is the use of telematic (monitoring) system to monitor persons, vehicles and objects which records, identifies and manages information shared controller and thus ensuring a much greater reliability, accuracy and security systems as they offer only to control access. moreover, it informs the attempt of unauthorized persons or other unusual events and consequently prevent...